Fault detection, supervision and safety of technical processes 2006 : a proceedings volume from the 6th IFAC symposium, SAFEPROCESS 2006, Beijing, P.R. China, August 30 - September 1, 2006 /: a proceedings volume from the 6th IFAC symposium, SAFEPROCESS 2006, Beijing, P.R. China, August 30 - September 1, 2006. (2007) - Unknown
No abstract available